The influence of leverage, company size, audit committee, free cash flow, and managerial ownership on earnings management - Wulandari, Riska Tri; Kusumawati, Eny (Junal Ilmu Manajemen, 2024)
This research analyzes the influence of leverage, firm size, audit committee, free cash flow, and managerial ownership on earnings management, which is the objective of this study. The sample selection method uses purposive sampling techniques on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. The sample consists of 130 companies with a total of 390 data points. The data analysis technique used is multiple linear regression with SPSS version 25. The results of the study provide empirical evidence that firm size and managerial ownership affect earnings management, while leverage, audit committee, and free cash flow do not affect earnings management.